Assessment of Fibrotic Liver Regeneration After Partial Hepatectomy With Intravoxel Incoherent Motion Diffusion-Weighted Imaging: An Experimental Study in a Rat Model With Carbon Tetrachloride Induced Liver Injury - Xie, Shuangshuang; Qiu, Caixin; Sun, Yajie; Yu, Yongquan; Hu, Zhandong; Zhang, Kun; Chen, Lihua; Cheng, Yue; Bao, Mingzhu; Zhang, Quansheng; Zhu, Jinxia; Grimm, Robert; et al. (Frontiers in Physiology, 2022)
Purpose To determine whether intravoxel incoherent motion (IVIM) parameters correlate with liver regeneration and function recovery after partial hepatectomy (PH) in rats with carbon tetrachloride (CCl4)-induced liver fibrosis. Methods Sixty-two adult Sprague-Dawley rats were divided into the control group and the fibrosis group with CCl4 injection for 8 weeks. At the end of the 8th week, all rats received left lateral lobe liver resection. Within each group, IVIM imaging (n=10/group) and histologic and biochemical analyses (n=3/group/time point) were performed pre- and post-PH (on days 1, 2, 3, 5, 7, 14, and 21). Differences in liver IVIM parameters and correlation between IVIM parameters and Ki-67 indices, hepatocyte diameter, alanine transaminase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBil) values were analyzed. Results Post-PH, liver true diffusion coefficient (D) values decreased and pseudodiffusion coefficient (D*) and perfusion fraction (PF) values increased, then recovered to pre-PH levels gradually in both fibrosis and control rats. PF in fibrosis group were significantly higher than in controls from 3 to 21 days (P < .05). In fibrosis rats, both Ki-67 indices and hepatocyte diameters increased, and a strong correlation was found between PF and Ki-67 indices (r = -0.756; P = .03), D* and PF values and ALT, AST, and TBil values (r = -0.762 to -0.905; P < .05). In control rats, only hepatocyte diameters increased, and all IVIM parameters correlated well with hepatocyte diameters, ALT, AST and TBil values (r = 0.810 to -1.000; P < .05). Conclusion The regeneration pattern in fibrotic liver tissue was different compared with control livers. IVIM parameters can monitor liver regeneration and functional recovery noninvasively after PH.